Pengaruh Tindakan Hemodialisa Terhadap Perubahan Tekanan Darah Pada Klien Gagal Ginjal Kronik di RSU Royal Prima Medan - Andini Amelia Futri; Regina Desni Ndruru; Lilis Suryani Siburian; Irwansyah Putra; Ivan Kristian Daeli; Karmila Br Kaban (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Chronic kidney disease, also known as CKD refers to an irreversible decline, in kidney function. It affects the bodys balance, electrolyte levels and metabolism. Elevated urea levels are an outcome of this condition (Desfrimadona, 2016). Chronic renal failure is when kidney function deteriorates for than three months. Patients undergoing hemodialysis typically have sessions lasting from twelve to fifteen hours per week or three to four hours per session. The aim of this research is to investigate the effectiveness of hemodialysis and changes in blood pressure among patients undergoing hemodialysis at RSU Royal Prima Medan in 2024. The study examined how blood pressure fluctuates in individuals with failure both before and after hemodialysis, through an observational study design. Based on respondent data and haemodialysis procedures in the haemodialysis unit of RSU Royal Prima Medan, it shows a Z- score of -3.464 and a P-value of 0.001 because 0,001 0.05, it can be concluded that haemodialysis at RSU Royal Prima Medan affects changes in blood pressure in patients with chronic renal failure.                                                                       Keywords: Haemodialysis, Kidney Failure, Blood Pressure  ABSTRAK Gangguan ginjal kronis, juga dikenal sebagai GGK mengacu pada penurunan fungsi ginjal yang tidak dapat diubah. Ini mempengaruhi keseimbangan tubuh, kadar elektrolit dan metabolisme. Peningkatan kadar urea adalah akibat dari kondisi ini (Desfrimadona, 2016). Gagal ginjal kronis terjadi ketika fungsi ginjal memburuk selama lebih dari tiga bulan. Pasien yang menjalani hemodialisis biasanya menjalani sesi yang berlangsung antara dua belas hingga lima belas jam per minggu atau tiga hingga empat jam per sesi.  Maksud riset ini ialah guna melihat keefektivan hemodialisis dan berubahnya tensi pada pasien yang menjalani hemodialisis di RSU Royal Prima Medan pada tahun 2024. Penelitian ini mengkaji bagaimana fluktuasi tekanan darah pada individu yang mengalami kegagalan baik sebelum maupun sesudah hemodialisis, melalui studi observasional cross section. Berdasarkan data responden dan prosedur hemodialisis di unit hemodialisis RSU Royal Prima Medan menunjukkan Z-score -3,464 dan P- value 0,001 sebab 0,001 0,05 hingga bisa dibuat simpulan jika hemodialisis di RSU Royal Prima Medan berpengaruh terhadap perubahan tekanan darah terhadap pasien GGK. Kata kunci: Hemodialis; Gagal Ginjal; Tekanan Darah.